Analisis Putusan Hakim Tentang Persetujuan Menikahi Wanita PNS Menjadi Istri Kedua Persepektif Maslahah Mursalah: (Studi Putusan Nomor 230/ Pdt.G/2024/PA.Plk) - Muhammad Afriza Rifandy; Syaikhu; Baihaki (Maqasid: Jurnal Studi Hukum Islam, 2025)
Abstract:This study examines the juridical considerations of the Religious Court judge in Palangka Raya in granting a civil servant’s (PNS) request for permission to practice polygamy, viewed through the lens of maslahah mursalah. The research focuses on the case decision Number 230/Pdt.G/2024/PA.Plk. Polygamy for civil servants is strictly regulated under both Islamic law and Indonesian positive law, particularly Government Regulation No. 45 of 1990 as an amendment to Government Regulation No. 10 of 1983. This study employs a normative and sociological juridical approach, using qualitative analysis of the court decision and the legal basis considered by the judge. The findings reveal that the judge considered various formal and material legal aspects, including the requirements set forth in the Compilation of Islamic Law and civil service regulations, as well as the interests of the wife and children. From the perspective of maslahah mursalah, the decision reflects the judge’s effort to balance legal texts with public interest considerations not explicitly mentioned in the scriptures, but relevant to social context and substantive justice. Therefore, the judge’s consideration in this case is not merely legalistic but also takes into account broader ethical and humanitarian dimensions. Keywords: Polygamy, Civil Servant, Maslahah Mursalah, Religious Court, Juridical Consideration.